Social reproduction and health: contributions from Breilh and Lukács to social thinking in collective health - Diego de Oliveira Souza (Revista Brasileira de Enfermagem, 2025)
ABSTRACT Objective: To analyze the relationship between social reproduction and health based on the theories of Jaime Breilh and Georg Lukács. Methods: This is a theoretical-conceptual study grounded in the immanent analysis of works by these authors. Results: It was found that, for Breilh, social reproduction establishes the dimensional frameworks for the social determination of health: general, particular, and individual. The author also defines essential principles for transforming life: sustainability, sovereignty, solidarity, and integral security. Lukács, in turn, emphasizes the mediation between the reproduction of individuals and society, highlighting the primacy of labor, which produces use-value. Within this relationship, alienating mediations may emerge, leading to human degradation, including health impacts. Final considerations: Both perspectives offer elements for rethinking health practices. Despite their differences, they critique the structural inequalities inherent in the capitalist mode of production and their repercussions on health.